MODERATION IN INDONESIAN TAFSIR: CRITICAL DISCOURSE ANALYSIS OF THE TERMS OF UMMATAN WASATAN IN THE AL-QUR’AN DAN TERJEMAHANNYA BY THE MINISTRY OF RELIGION OF THE REPUBLIC OF INDONESIA - Cholily, Naufal (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2023)
Various kinds of religious issues in the context of the state, such as intolerance between religious communities, have made the state formulate a program of religious moderation through the Kementerian Agama RI in 2019. The importance of this program can be seen from the inclusion of religious moderation in the Konsep Rencana Pembangunan Jangka Menengah Nasional 2020-2024 by Bappenas. On the other hand, the Ministry of Religion has been producing Qur’anic literature for a long time through the Al-Qur’an dan Terjemahnya, Al-Qur’an dan Tafsirnya, Tafsir Tematik Moderasi Beragama, and others. This article attempts to trace the meaning of religious moderation through Al-Qur’an dan Terjemahnya from time to time (1990 and 2019 editions), with the following questions: How do the products of the Al-Qur’an Terjemah Kemenag discuss religious moderation? The meaning of the word tawasut will be traced from the Al-Qur’an dan Terjemahnya from time to time. This research is a text analysis (content analysis) with a qualitative research method that comes from two main data sources, namely primary data and secondary data. Furthermore, processing the data is done by using the literature mapping technique. The conclusions obtained from these two editions do not exist in a vacuum. Texts were produced according to the context and socio-political setting of the time. After analyzing through text dimensions, discursive practices and sociocultural practices, it was found that the construction of ideology in the structure of the text can be seen in the translation changes in the two verses. Expanding the meaning and euphemism of the terms used responds to the context surrounding the Qur’an and its translation by the Kementerian Agama RI. The production and consumption of texts can then be seen from government policies through the Kementerian Agama in the socialization of moderation in all lines of people’s lives, in religion, intellectuals and society.